Torsion of a wandering spleen in a young thalassemic patient - Limchareon, Sornsupha; Chaivanit, Trakarn; Hirunpattarasilp, Wiramon (Journal of Emergency and Critical Care Medicine, 2018)
A 19-year-old Asian, thalassemic female presented with abdominal pain for 3 days. The pain started in the supraumbilical area and migrated to the suprapubic area, with nausea, anorexia, and diarrhea. On pelvic examination, purulent discharge was found with cervical motion tenderness. She was treated as a pelvic inflammatory disease.